Upaya Guru Pendidikan Agama Islam dalam Pembelajaran Akhlak pada Siswa Tunanetra di Kelas 4 SD Atta’zhimiyah Bandung - Karlina Nurhasanah Lina; A. Mujahid Rasyid; Nurul Afrianti (Bandung Conference Series: Islamic Education, 2023)
Abstract. Karlina nurhasanah. (10030118189). Thesis of PAI Study Program, Faculty of Tarbiyah and Teacher Training, Islamic University of Bandung. 2023. Moral learning must be carried out in all schools and given to all students, including those with special needs such as blindness. Moral learning is required or carried out not only looking at limitations or looking at age. like this research at SD Atta'zhimiyah Bandung inclusive school which has blind students and researchers are interested in how the teacher's efforts in learning morals in blind students. This research uses qualitative research with a case study method on one blind student located at SD Atta'zhimiyah Bandung. The data sources used are primary data and secondary data. The data collection techniques used were interviews, observation and documentation. The data analysis technique uses the Miles and Humberman technique (1992, p. 20), namely data collection from data analysis activities, data reduction, data verification, and data presentation. The results of this study can be described that: 1). Moral learning planning for blind students is in accordance with the lesson plan, syllabus and in accordance with the 2013 curriculum. 2). the implementation of moral learning for blind students, namely, the utilization of senses that are still functioning, the use of media in moral learning, and effective learning skills for blind students. 3). Evaluation in learning morals in blind students, namely daily tests, UTS, and UAS using 3 techniques, namely written tests, oral tests, and assignments. 4). Obstacles in learning morals in blind students have several factors. 5). Analysis of moral learning in blind students is good enough in improving moral learning. Moral learning planning for blind students at SD Atta'zhimiyah Bandung relies on the 2013 curriculum, which has lesson plans and syllabus. This is also followed by the implementation of moral learning for blind students in the opening, core and closing activities. After planning and implementation, it is inseparable from evaluation so that teachers can find out the understanding of blind students. And every learning must have obstacles in achieving these goals, therefore an analysis of moral learning is held for blind students. Abstrak. Karlina Nurhasanah. (10030118189). UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBELAJARAN AKHLAK PADA SISWA TUNANETRA DI KELAS 4 SD ATTA’ZHIMIYAH BANDUNG. Skripsi Program PAI, Fakultas Tarbiyah san Keguruan, Universitas Islam Bandung. 2023. Pembelajaran akhlak harus dilakukan diseluruh sekolah dan diberikan kepada semua siswa, tak terkecuali yang memiliki kebutuhan khusus seperti tunanetra. Pembelajaran akhlak dilakukan tidak hanya memandang keterbatasan tetapi belajar suatu hal yang sangat wajib untuk dilakukan pada semua orang. seperti penelitian ini di sekolah inklusi SD Atta’zhimiyah Bandung yang memiliki siswa tunanetra dan peneliti tertarik dengan bagaimana upaya guru dalam pembelajaran akhlak pada siswa tunanetra. Penelitian ini menggunakan penelitian kualitatif dengan metode studi kasus pada satu siswa tunanetra yang berlokasi di sekolah dasar (SD) Atta’zhimiyah Bandung. Sumber data yang digunakan yaitu data primer dan data sekunder. Teknik pengumpulan data yang dilakukan yaitu wawancara mendalam, observasi dan dokumentasi. Teknik analisis data menggunakan reduksi data, verivikasi data, dan penyajian data. Hasil penelitian ini dapat di dekripsikan bahwa: 1). Perencanaan pembelajaran akhlak pada siswa tunanetra sesuai dengan RPP, Silabus dan sesuai dengan kurikulum 2013. 2). Pelaksanaan pembelajaran akhlak pada siswa tunanetra yaitu, pemanfaatan indera yang masih berfungsi, penggunaan media dalam pembelajaran akhlak, dan keterampilan belajar yang efektif bagi siswa tunanetra. 3). Evaluasi dalam pembelajaran akhlak pada siswa tunanetra yaitu ulangan harian, UTS, dan UAS dengan menggunakan 3 teknik yaitu tes tulis, tes lisan, dan penugasan. 4). Hambatan dalam pembelajaran akhlak pada siswa tunanetra memiliki beberapa faktor. 5). Analisis Pemelajaran akhlak pada siswa tunanetra sudah cukup baik dalam meningkatkan pembelajaran akhlak. Perencanaan pembelajaran akhlak pada siswa tunanetra di SD Atta'zhimiyah Bandung merancu pada kurikulum 2013, yang memiliki RPP dan silabus. Hal ini pun dilanjutkan dengan Pelaksanaan Pembelajaran akhlak pada siswa tunanetra pembuka, kegiatan inti dan penutup. Setelah diadakannya perencanaan dan pelaksanaan maka tidak terlepas dari evaluasi agar guru dapat mengetahui pemahaman siswa tunanetra. Dan setiap pembelajaran pasti memiliki hambatan dalam mencapai tujuan tersebut, maka dari itu diadakannya analisis pembelajaran akhlak pada siswa tunanetra.